2016
DOI: 10.1175/jamc-d-15-0314.1
|View full text |Cite
|
Sign up to set email alerts
|

Local Meteorological and Large-Scale Weather Characteristics of Fog over the Grand Casablanca Region, Morocco

Abstract: Using a fog event approach, the local meteorological and synoptic characteristics of fogs that formed over the Grand Casablanca (GCB) region during a 9-yr period (2001–09) are investigated. A climatological study of fog, with emphasis on the fog temporal variability and spatial distribution, is carried out on the basis of hourly surface meteorological observations at two synoptic stations in the region. The fog events are classified into fog types, using an objective classification algorithm, and are character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…However, despite these limitations, this study demonstrated that besides advective fog, radiation and mixed fog occurred regularly in this section of the Namib Desert, at least during the observation period. Furthermore, stable isotope analysis of fog suggests co-occurrence of different types of fog during what appears as a single fog event over a large geographic area, similar to the observations of Bari et al (2016) in Morocco. This suggests that our current understanding of fog dominated ecosystems could be overly simplistic thus there is a need for further studies to understand spatial variability of fog types, their significance to ecohydrology and how shifts or changes might affect the composition of endemic flora and fauna in the future.…”
Section: The Relationships Between Radiation Fog Isotopic Compositionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, despite these limitations, this study demonstrated that besides advective fog, radiation and mixed fog occurred regularly in this section of the Namib Desert, at least during the observation period. Furthermore, stable isotope analysis of fog suggests co-occurrence of different types of fog during what appears as a single fog event over a large geographic area, similar to the observations of Bari et al (2016) in Morocco. This suggests that our current understanding of fog dominated ecosystems could be overly simplistic thus there is a need for further studies to understand spatial variability of fog types, their significance to ecohydrology and how shifts or changes might affect the composition of endemic flora and fauna in the future.…”
Section: The Relationships Between Radiation Fog Isotopic Compositionsupporting
confidence: 74%
“…hours (Bari et al, 2016). However, although Volgefederberg showed an initial increase in specific humidity on the 16 th June 2016, by end of the daylight hours this had decreased and only increased during the night by 0.8 g kg -1 just before fog onset at 0:00 hrs (Fig.…”
Section: Classification Of Fog On the 17mentioning
confidence: 89%
See 1 more Smart Citation
“…Adverse visibility in foggy conditions often leads to serious accidents for air, road and marine traffic. Therefore, fog is a potentially disastrous weather phenomenon that is of widespread concern (e.g., Taylor, 1917;Musson-Genon, 1987;Duynkerke, 1991;Koracin et al, 2001;Bergot et al, 2005;Roquelaure et al, 2009) and has been studied extensively from different points of view (Gultepe et al, 2007): climatology studies (e.g., Tarif and Rasmussen, 2007;Bari et al, 2016), remote sensing studies (e.g., Cermak and Bendix, 2007), statistical forecasting (e.g., Hilliker and Fritsch, 1999;, and numerical modeling (e.g., Cuxart and Jiménez, 2012;Bergot et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…It results from nighttime radiative cooling of moist air that has been advected over land from the ocean or from any large water body during the previous daylight hours (Ryznar, 1977). Bari et al (2016) have performed a climatological study in the Grand Casablanca region, Morocco. They show that advection-radiation fog is the most common fog type over this region.…”
Section: Introductionmentioning
confidence: 99%